Sinking into the unthinkable: using extreme fiction to study future crises - Buchanan, David A.; Hällgren, Markus; Jané, Sophie E (Emerald, 2026)
Purpose: We aim to show how extreme fiction can be used to study possible future extreme events, allowing researchers to get “up close” to potentially dangerous settings. Design/methodology/approach: How can research help to understand a world that has become more unpredictable and dangerous? We assess the use of fiction as research material and explore dramatized movie accounts of possible future accidents, crises and disasters through “extreme fiction” – a genre which has been underutilized. We assess the benefits and limitations of using extreme fiction as a research resource. An example of how extreme fiction can challenge assumptions and generate novel theoretical insights is presented. Findings: Extreme fiction can help us to anticipate, understand and prepare for possible future crises. This medium can also prompt challenges to taken-for-granted assumptions and trigger fresh theoretical insights. Research limitations/implications: The use of extreme fiction as research material is limited by concerns of credibility, evidential boundaries and selectivity. We suggest ways of responding to these challenges. Practical implications: This approach gives researchers an additional lens through which to explore future accidents, crises and disasters. Improved understanding improves our ability to anticipate, plan and respond more effectively to such events. Social implications: Exposure to fictional crises in movies and other media can increase resilience to actual events. Disaster movies can be seen as educational as well as entertaining. Originality/value: Implausible, unrealistic, exaggerated and sensationalized, fictional accounts of extreme events have been overlooked by research. But to develop understanding of future possibilities and prompt fresh thinking, implausibility is a useful property of these accounts.
Keywords: Crisis management; Disasters; Extreme contexts; Extreme events; Extreme fiction; 35 Commerce, Management, Tourism and Services; 3505 Human resources and industrial relations; 3507 Strategy, management and organisational behaviour